A seminal perspective on the role of chondroitin sulfate in biomineralization. (15th June 2023) - Hao, Jia-xin; Wan, Qian-qian; Mu, Zhao; Gu, Jun-ting; Yu, Wei-wei; Qin, Wen; Li, Yu-tao; Wang, Chen-yu; Ma, Yu-xuan; Jiao, Kai; Tay, Franklin; Niu, Lina
Abstract: Chondroitin sulfate (CS) is an important extracellular matrix component of mineralized tissues. It participates in biomineralization, osteoblast differentiation and promotes bone tissue repair in vitro . However, the mechanism in which CS functions is unclear. Accordingly, an in-depth investigation of how CS participates in mineralization was conducted in the present study. Chondroitin sulfate was found to directly induce intrafibrillar mineralization of the collagen matrix. The mineralization outcome was dependent on whether CS remained free in the extracellular matrix or bound to core proteins; mineralization only occurred when CS existed in a free state. The efficacy of mineralization appeared to increase with ascending CS concentration. This discovery spurred the authors to identify the cause of heterotopic ossification in the Achilles tendon. Chondroitin sulfate appeared to be a therapeutic target for the management of diseases associated with heterotopic calcification. A broader perspective was presented on the applications of CS in tissue engineering. Graphical abstract: Unlabelled Image